Maternal and newborn health needs for women with walking disabilities; "the twists and turns": a case study in Kibuku District Uganda - Rebecca R. Apolot; Elizabeth Ekirapa; Linda Waldman; Rosemary Morgan; Christine Aanyu; Aloysius Mutebi; Evelyne B. Nyachwo; Gloria Seruwagi; Suzanne N. Kiwanuka (BMC, 2019)
Abstract Background In Uganda 13% of persons have at least one form of disability. The United Nations' Convention on the Rights of Persons with Disabilities guarantees persons with disabilities the same level of right to access quality and affordable healthcare as persons without disability. Understanding the needs of women with walking disabilities is key in formulating flexible, acceptable and responsive health systems to their needs and hence to improve their access to care. This study therefore explores the maternal and newborn health (MNH)-related needs of women with walking disabilities in Kibuku District Uganda. Methods We carried out a qualitative study in September 2017 in three sub-counties of Kibuku district. Four In-depth Interviews (IDIs) among purposively selected women who had walking disabilities and who had given birth within two years from the study date were conducted. Trained research assistants used a pretested IDI guide translated into the local language to collect data. All IDIs were audio recorded and transcribed verbatim before analysis. The thematic areas explored during analysis included psychosocial, mobility, health facility and personal needs of women with walking disabilities. Data was analyzed manually using framework analysis. Results We found that women with walking disabilities had psychosocial, mobility, special services and personal needs. Psychosocial needs included; partners', communities', families' and health workers' acceptance. Mobility needs were associated with transport unsuitability, difficulty in finding transport and high cost of transport. Health facility needs included; infrastructure, and responsive health services needs while personal MNH needs were; personal protective wear, basic needs and birth preparedness items. Conclusions Women with walking disabilities have needs addressable by their communities and the health system. Communities, and health workers need to be sensitized on these needs and policies to meet and implement health system-related needs of women with disability.